2011
DOI: 10.1007/s13337-011-0034-3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Hepatitis B Virus Genotypes and Its Association with Severity of Liver Disease in Patients with Chronic Hepatitis B in Uttar Pradesh, India

Abstract: The present study was designed to investigate the distribution of genotypes and its association with severity of liver disease in patients with Chronic Hepatitis B (CHB) in Uttar Pradesh, India. One hundred five HBsAg positive patients were selected for the study. The DNA was extracted by using pure viral DNA extraction kit. The genotype of Hepatitis B virus (HBV) was identified by using polymerase chain reaction-based restriction fragment length polymorphism (PCR-RFLP) method, by using AvaII and DpnII restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…These studies have mostly looked at association between the specific HBV genotypes and liver disease severity. A few studies from India reported that genotype D was associated with severe disease compared with genotype A [22,23]. However, another study revealed no difference in clinical and histological severity between genotypes A and D [24].…”
Section: Influence Of Hbv Genotypes On the Natural History Of Chronicmentioning
confidence: 98%
“…These studies have mostly looked at association between the specific HBV genotypes and liver disease severity. A few studies from India reported that genotype D was associated with severe disease compared with genotype A [22,23]. However, another study revealed no difference in clinical and histological severity between genotypes A and D [24].…”
Section: Influence Of Hbv Genotypes On the Natural History Of Chronicmentioning
confidence: 98%
“…[ 6 33 38 40 41 43 ] Globally, HBV NAT testing has been gaining acceptance for several reasons including: (a) HBsAg, the commonly diagnosed serology marker, unlike antibody markers, is a transiently expressed viral protein detectable late in infection at 30 days and lasting up to 63 days,[ 10 31 ] (b) mutations in HBsAg result in serology misses,[ 33 ] (c) in certain genotypes such as G, the HBsAg negative WP is substantially prolonged and will be missed by serology tests,[ 37 ] (d) in countries with moderate to high HBV prevalence, positivity for antibody markers will be high resulting in high discard rate, which is not viable for blood supply[ 29 30 44 ] and finally (e) several studies have demonstrated the benefit of high sensitivity ID NAT testing to detect WP and OBI infections. [ 30 ] Factors that necessitate highly sensitive HBV NAT testing in India include (a) relatively high HBsAg positivity of 1.2% in the donor population,[ 8 ] (b) a 10-30% anti-Hepatitis B core (HBc) prevalence,[ 44 ] (c) the major HBV type being Genotype D, followed by A and C,[ 45 46 ] with genotypes D and A documented to remain at low viral load[ 6 34 ] and (d) the additional association of HBV genotype D with high occult HBV infections, which is characterized by fluctuating low viral load. [ 6 35 39 41 42 ]…”
Section: Hbv Nat Blood Screening Detection Failuresmentioning
confidence: 99%